INTERNAL FACTORS, PERSONAL PREREQUISITES IN YOUNGER SCHOOL CHILDREN (European Journal of Interdisciplinary Research and Development, 2022)
This article describes in detail the internal factors, personal conditions, the development of the creative process in younger students, the child's reflection on his life values, personal qualities, and the further development of intellectual abilities in children.